Rapid Assessment of CRISPR Transfection Efficiency and Enrichment of CRISPR Induced Mutations Using a Dual-Fluorescent Stable Reporter System - Shalaby, Karim E.; Aouida, Mustapha; Gupta, Vijay; Ghanem, Simona S.; El-Agnaf, Omar M. A. (Frontiers in Genome Editing, 2022)
The nuclease activity of the CRISPR-Cas9 system relies on the delivery of a CRISPR-associated protein 9 (Cas9) and a single guide RNA (sgRNA) against the target gene. CRISPR components are typically delivered to cells as either a Cas9/sgRNA ribonucleoprotein (RNP) complex or a plasmid encoding a Cas9 protein along with a sequence-specific sgRNA. Multiple transfection reagents are known to deliver CRISPR-Cas9 components, and delivery vectors are being developed for different purposes by several groups. Here, we repurposed a dual-fluorescence (RFP-GFP-GFP) reporter system to quantify the uptake level of the functional CRISPR-Cas9 components into cells and compare the efficiency of CRISPR delivery vectors. Cells stably expressing this dual-fluorescent reporter construct facilitated a direct quantification of the level of the internalized and functional CRISPR-Cas9 molecules into the cells without the need of co-transfecting fluorescently labeled reporter molecules. Additionally, targeting a reporter gene integrated into the genome recapitulates endogenous gene targeting. Thus, this reporter could be used to optimize various transfection conditions of CRISPR components, to evaluate and compare the efficiency of transfection agents, and to enrich cells containing desired CRISPR-induced mutations. Using this system, we developed a novel and rapid cell-based microplate reader assay that makes possible real-time, rapid, and high throughput quantification of CRISPR nuclease activity.